Legal Comparisons Regarding the Content of Franchise Prospectus in Legal System of United States of America, Australia, Indonesia For Legal Protection of Frait Recipients in Indonesia - Rika Githamala Ginting (Budapest International Research and Critics University, 2021)
The prospectus document is given as a consideration for the franchisee whether they want to participate in operating the franchise or not. Apart from being used as a medium to find out information about franchises, this prospectus is also a form of legal protection for franchisees. Article 7 of the Government Regulation on franchising regulates clauses that must be included in the prospectus. The regulations governing minimal clauses in this prospectus are quite minimal. Compared to the United States, which is the originating country for franchising and Australia, which follows the United States in regulating its franchises, Indonesia is still far behind in the preparation of its prospectus documents. The method used is the legal comparative research method because it is used to compare regulations in a country with other countries. The research results show that each prospectus minimum clause in Indonesia has its own objectives in terms of protecting prospective franchisees and franchisees. There are differences between the clauses that must be listed in the prospectus in the United States, Australia and Indonesia, where there are clauses that are regulated in the United States and Australia which are not regulated in the minimum clause of the prospectus in Indonesia, although there are differences, but there are also clauses that are the same regulated in the three countries, it's just that the explanation of the provisions has differences. Regarding whether Indonesia's prospectus is capable of, Indonesia's minimum clause has not been able to provide protection for franchisees in Indonesia.